How Does the Attitude to Sustainable Food Influence the Perception of Customers at the Point of Sale? - an Eye-Tracking Study - Julia Lamberz; Thorsten Litfin; Özlem Teckert; Gunther Meeh-Bunse (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
mportance of sustainable consumption. Consumers associate sustainable products with ecological and regional production including a high credibility. In order to take advantage of this trend manufacturers of sustainable foods must communicate the sustainability of their products via packaging and displays at the point of sale. The objective of this article is to examine how the design of display elements succeeds in conveying sustainability for a new organic juice. In addition, the perception of individual design elements of sustainable products is determined. To this end, a field study was carried out in a supermarket combining eye-tracking technology with a survey of 32 customers. At the entrance, customers were asked to buy a variety of the newly introduced "Emsländer" organic juice, and then participate in the survey. The results demonstrate that customers with a positive attitude towards sustainable food fixate individual display elements referring to sustainability components for longer and remember product features better. Hence, the positive attitude towards sustainable food results in a higher visual attention at the point of sale. These findings provide recommendations for the design of the display.
Keywords: M31; M37; 330; consumer behaviour; eye-tracking; sustainability; visual merchandising; visual attention